Bienestar laboral de los docentes y administrativos de la Universidad de la Costa C.U.C. en el 2013 (2014)
The main purpose of this study was to describe the occupational well-being of the full time teachers and administrative personnel from the University “Universidad de la Costa – C.U.C.” The specific objectives were to determinate the psychosocial well-being factors and identify the collateral effects. This project is based on a quantitative investigation. The population was integrated and constituted by a representative sample of 254 people between full time teachers, scholars and administrative personnel of the University “Universidad de la Costa – C.U.C.” In order to accomplish the objectives for this investigation, the Occupational Wellbeing Questionare by Joseph Blanch, Miguel Shagun and Genis Cervantes, was applied; this is a theoretical model of occupational well-being which includes a descriptive dimension of the Psychosocial Well-being (integrated by affections, skills and expectations) and the other category of colateral effects (somatization, burnout and alientation) to employees in different departments and faculties. The question about satisfaction and work-quality is emphasized by the results with the highest score by the scholars, in the second place the administrative personnel, which manifested having experimented satisfaction and work-quality in the Institution, but suggesting actions of improvement; the last group was the full time teachers who generally scored lower than the other two groups, maybe because they manifested some indicators of favorability based on their work conditions and how they feel about their job. This can infer the necessity to revise the upcoming actions, in order to increase the levels of acceptance and compromise with the system developed by the University. It is concluded that the well-being is an important aspect to improve the quality of the employees working life and to make possible having a better course of action developed by the University.